Green Transition through Energy Inclusion Communities and DAOs (with appended list of exemplary organizations) - Korhonen Outi; Ala-Ruona Jari (Turun yliopisto, 2025)
This paper questions the ‘prosumeristic’ participation of individuals, communities, consumers and citizens in the green energy transition. That is, as often called for, consumers, citizens, individuals, and their groups and communities could become influential decision-makers in energy production systems alongside the traditional model of large energy production and distribution companies. This paper defines a virtual energy inclusion community (VEICO) as a collective entity that leverages Web3-innovations such as decentralized autonomous organizations (DAOs) with the purpose of facilitating equitable participation in energy production and consumption across different socio-economic and geographical landscapes. Such communities purport to align with global sustainability goals and transcend traditional barriers, and to offer a more holistic and democratic approach to energy management. Although energy communities and energy-DAOs, may not result in the achievement all of the renewable energy goals, their potential as catalysts for a more participatory energy market structure may be quite significant. The long-term economic, market and societal potential of energy communities and their role in decentralization merits to be explored. The paper presents the example of Mari, a participant in an hypothetical VEICO, and includes an appendix listing energy-community-enabling DAOs.